Seismic response analysis of long-span and asymmetrical suspension bridges subjected to near-fault ground motion. (September 2020) - Zheng, Shi-xiong; Shi, Xin-hu; Jia, Hong-yu; Zhao, Can-hui; Qu, Hong-lue; Shi, Xin-long
Highlights: The seismic responses of long-span and asymmetrical suspension bridges subjected to near-fault ground motions are investigated systematically and comparatively. The influence of velocity pulse effect, site effect, and structure-soil interaction on the seismic responses of interests in the suspension bridge seismic analysis is considered and analyzed. Recommendations for the seismic design of long-span and asymmetrical suspension bridges subjected to near-fault ground motions. Abstract: The objective of this paper is to investigate the seismic responses of long-span and asymmetrical suspension bridges subjected to four intensity level (Small, moderate, huge, and super earthquakes) of near-fault ground motions. A typical suspension bridge located in Yunnan province of China is selected herein to study the dynamic response of long-span and asymmetrical suspension bridges. And the corresponding finite element model based on the platform of OpenSEES is established to consider the influence of velocity pulse effect, site effect, and structure-soil interaction on the seismic responses of interests e.g., tower, girder, and pile, etc., in the suspension bridge seismic analysis. Besides the near-field and far-field ground motion records are employed from the data base in Pacific Earthquake Engineering Research Center of the United States for comparison analysis. Finally numerical analysis results have suggested that the influence of near-fault effect on the response of long-span and asymmetrical suspension bridges and the different dissipation capacity of nonlinear viscous damper in various intensity levels should be paid more attention to in the seismic design of this type bridges.